The range of philosophical aphorisms in the psychological exploration of “Shchodennyk strachenoyi” by Mariya Matios (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This article reveals creative linguistic potential of Mariya Matios, her ability of sentences constructing, which over time can break away from the original contexts and be used as ready set expressions (though some of them already exist so). If necessary these statements can run themselves according to the communicative needs in various communicative situations. The paper itself focuses on aphorisms that illustrate the wide philosophical range. Aphorisms are obviously not only the means of ideological reflections of the main character in the psychological exploration of “Shchodennyk strachenoyi”. The researcher’s attention is paid on the literal and semantic plans of “existence” concept presented by the nuclear and peripheral concepts like “life”, “death”, “human”, “woman”, “man”, ‘love” etc.The represented research investigates semantic and psychological senses in aphoristic statements that clearly reflect the individual author’s understanding of human nature in general and the woman’s nature in particular. These statements also point on the ways of verbalizing the ideas about the modern world and the place of women in it. Moreover aphorisms actualize the “existence” concept distinguishing first the female existence.
Keywords: aphorism; aphoristic statement; opinions; psychological research; semantic content